Politics on the margins: A case study of neoliberal subject formation in the popular quarters of Cairo - Al-Samragy, Bassem Zakaria (AUC Knowledge Fountain, 2018)
This thesis focuses on one instance on the margin of the events of January 2011 in Egypt. It aims to conceptualize the moment of January 28th as a moment of popular contention through the context of neoliberal subject formation. In doing so, this thesis revisits the role and the nature of the neoliberal state emerging from the welfare state in contemporary Egypt. Against the backdrop of governmentality as a conceptual framework, this study will investigate how neoliberalism informs our experience of time and space in everyday life; and, more specifically, how the process of neoliberal subject for mation shapes the public space of popular quarters of Cairo in a way that made the moment of January 28th inevitable. Following governmentality as a conceptual framework, this thesis provides different layers of contextualization and analysis to the neighborhood of Al-Mataria, i.e., historical, social, political, economic and theoretical. Hence, this thesis ventures beyond targeted approaches that tend to focus on moments of popular explosion in relative disregard for the underlying factors that lend to the ir explanation. By means of ethnography and qualitative inquiry, this study will explain the dynamics of Al-Mataria and unpack the logic of government there. Following the assumption that governing the space of Al-Mataria takes a hybrid form combining formal and informal techniques and networks, this study aims at observing closely how the state is both part of, and interacts with, the everyday life of the people, and how that dynamism creates specific types of state-society relations whose contradictions made the moment of contention possible. As such, this thesis provides us the chance to understand and reveal an oft-understudied background behind, yet also at the heart, of the 2011 Egyptian uprising more broadly.